Survival Strategies under Sanctions: Firm-Level Evidence from Iran - Iman Cheratian; Saleh Goltabar; Mohammad Reza Farzanegan (Center for Economic Studies and ifo Institute (CESifo), 2022)
Given the importance of firm strategic management in time of crises, this study investigates Micro, Small, and Medium Enterprises (MSMEs) survival strategies during the international sanctions against Iran. Using data from a questionnaire of 486 firms between December 2019 to September 2020, we found that firm strategies in reducing research and development (R&D) expenditures, marketing costs, and fixed/overhead costs and investing in information technology (IT) are positively related to their survivability. Conversely, managerial decisions to "reduce production" and "staff pay cut/freeze" have negative and significant impacts on a firm's ability to survive during sanctions. Moreover, micro firms are more resilient than their small and medium counterparts. The findings also confirm that age has a significant and positive impact on firm survival. Finally, the results show that having a business plan, access to finance and technology, owner education, export orientation, business networking and consulting services are the key drivers of withstanding the pressure from sanctions.
Keywords: F51; M13; L25; L26; 330; crisis; recession; sanction; survival strategies; firm; Iran